BİR BİLGÎ ETKİNLİĞİ OLARAK BİLİM VE SANAT - Adnan Ömerustaoğlu (Felsefe Dünyası)
This article discusses the facts, impressions and functions implied by science and art as epistemological activités. It also analyses the validity and truth of their judgments, social expectations, the impact of science and art in creating a common sense as well as their own history